1992
DOI: 10.1080/02652039209374117
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of protein‐bound furazolidone metabolites containing the 3‐amino‐2‐oxazolidinone side‐chain from liver, kidney and muscle tissues from pigs

Abstract: Ten 3-month-old pigs were treated with feed containing 300 mg furazolidone per kg for a period of 7 days, followed by withdrawal periods of 0, 1, 2, 3 or 4 weeks (two per group). The treatment resulted in the formation of protein-bound metabolites containing an intact 3-amino-2-oxazolidinone (AOZ) side-chain that could be chemically released and then detected in liver, kidney and rump muscle tissues even 4 weeks after dosing. In tissues from animals killed at the end of the medication period, 993, 600 and 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 5 publications
4
56
0
Order By: Relevance
“…Although the metabolism of nitrofurans is not well documented, a suggested mechanism is through cleavage of the nitrofuran ring, leaving the specific tail group covalently bound to tissue (Leitner et al, 2001). In vivo, these metabolites can be released by natural stomach acids (Hoogenboom et al, 1992); this fact is taken into consideration in the isolation of metabolites for residue analysis (see Chapter 7). Studies examining the bioavailability of nitrofuran metabolites have demonstrated the possibility of residual transfer to secondary species.…”
Section: Metabolism and Bioavailability Of Nitrofuransmentioning
confidence: 99%
“…Although the metabolism of nitrofurans is not well documented, a suggested mechanism is through cleavage of the nitrofuran ring, leaving the specific tail group covalently bound to tissue (Leitner et al, 2001). In vivo, these metabolites can be released by natural stomach acids (Hoogenboom et al, 1992); this fact is taken into consideration in the isolation of metabolites for residue analysis (see Chapter 7). Studies examining the bioavailability of nitrofuran metabolites have demonstrated the possibility of residual transfer to secondary species.…”
Section: Metabolism and Bioavailability Of Nitrofuransmentioning
confidence: 99%
“…Due to its carcinogenicity, the detection of furazolidone residual in the breeding and its adjacent environment is very important for controlling its usage and environmental level. Several methods have been developed to detect furazolidone, such as HPLC (Hoogenboom et al, 1992;GaleanoDı́az et al, 1997), LC-MS (McCracken and Kennedy, 1997), LC-MS/MS (Leitner et al, 2001), and ELISA (Diblikova et al, 2005;Li J. et al, 2010). However, HPLC, LC-MS, and LC-MS/MS are time-consuming, expensive, and requirement of sophisticated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…19 This can be explained because of the dehydration process needed to prepare the fishmeal. This methodology differs from simply adding AOZ to the feed, because AOZ from FZD-medicated animals is believed to be covalently linked to tissue proteins, thus resembling the trophic chain in a more accurate way.…”
Section: Discussionmentioning
confidence: 99%